Antibacterial and Antifungal Capacity of Three Commercially Available Mouthwashes with Different Concentrations of Chlorhexidine - Chavarría-Bolaños, Daniel (2021)
Chlorhexidine was introduced almost seven decades ago and has a myriad of applications in dentistry. Few studies have evaluated the antimicrobial and antifungal capacity of different concentrations of chlorhexidine mouthwashes. Therefore, the aim of this study, was to evaluate in vitro, the antibacterial and antifungal capacity of three commercially available mouthwashes in Costa Rica, with different concentrations of chlorhexidine, 0.12%, 0.06%, and 0.03%. The experimental method selected was the Kirby-Bauer method to evaluate the antibacterial and antifungal effect of each compound by measuring the inhibitory effect on Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Candida albicans strains, exposed to the antiseptic solutions. All samples showed some degree of antibacterial and antifungal effect. Even though we provide in vitro results, our findings are of relevance since all the species used in our experiment are microorganisms that may be present in dental plaque. Our results further support evidence that oral hygiene regimens may include mouthwashes with low doses of chlorhexidine and maintain reasonable antibacterial and antifungal efficacy.